AHP Algorithm for Indoor Air Pollution Detection and Evaluation System Design - Fan, Wen; Chang, Chengyang; Yao, Ning; Xu, Linxue; Ju, Hongyan (Informatica, 2023)
In order to extract a description of indoor air quality, the concentration of indoor pollutants needs to be obtained and then evaluated. Aiming at the existing indoor air quality monitoring and evaluation system, an AHP algorithm for the design of indoor air pollution detection and evaluation system is proposed, which combines the principles and methods of fuzzy mathematics to evaluate air quality in a confined environment. An experiment was carried out, using the analytic hierarchy process to assign weights. According to the principle of maximum subordination, comprehensive evaluation of air quality in a confined environment was carried out through fuzzy mathematical model. The experimental results show that the humidity value reached 54% RH when the temperature was 25°C, and the humidity value reached 60% RH when the temperature was 19°C. The evaluation results more scientifically reflect the true state of air quality.